PENGARUH PENERAPAN STRATEGI BELAJAR AKTIF TIPE PEER LESSON DISERTAI PETA PIKIRAN TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII SMPN 30 PADANG - Rahayu, Mega; Rismen, Sefna; Husna, Husna (STKIP PGRI Sumbar, 2013)
This research is motivated by low ability students mathematical communication skills. Communication skills requires students to state and interpret mathematical ideas orraly, in writing, or mendemonstrasi. Therefore the ability to communicate in mathematics became guidance. This study aims to determine whether the ability of students to use mathematical communication active type peer learning strategies lesson with mind maps better than that using conventional learning in class VIII SMPN 30 Padang. This type of research is experimental research, with the deseign of random design on the subject. Population in this study were all students of class VIII SMPN 30 Padang. The sampling technique is random sampling. Reseach instuments essai is a test. The data analisys which Â = 2.02 is greather Â it can be concluded that students mathematical communication skills of students who learning strategies type Peer Lesson with mind maps better than using the conventional learning in class VIII SMPN 30 Padang with the level of confidence 95%.